SINO-ITALIAN POLITICAL AND ECONOMIC COOPERATION: Perspectives and challenges - Popovic, Slobodan (Politeia, 2021)
The purpose of this article is to examine Sino-Italian political and economic cooperation. The first part of the paper reviews the still ongoing process of China`s ambitions to present itself as a ‘non-Other’ to the international society by carrying out economic development and political opening and offering the Belt and Road Initiative to international partners. However, Beijing still faces (un)justified accusation that it affects the implementation of the already established norms, principles and procedures of the international law, sustainable development, geopolitical order, and geoeconomic distribution of wealth. For the purpose of this research, our focus will be on Italian understanding of the maritime perspective of the Belt and Road Initiative. The second part examines tools that the two countries use for overcoming obstacles to political and economic cooperation, whilst striving not just to widen and strengthen mutual trust, sincerity, and pragmatism, but to protect national interests as well.